Front Cover. Issue 1 (January 2017) - Rutledge, Linda Y.; Desy, Glenn; Fryxell, John M.; Middel, Kevin; White, Bradley N.; Patterson, Brent R.
Abstract : The cover image, by Linda Rutledge et al., is based on the Biodiversity Research Patchy distribution and low effective population size raise concern for an at‐risk top predator, DOI:10.1111/ddi.12496 . Photo Credit: Michael Runtz.